PEMANFAATAN INTERNET SEHAT MENUJU GENERASI UNGGUL PADA DESA CENGKERING PEKAN KABUPATEN BATUBARA - Syafwan, Havid; Helmiah, Fauriatun; Putri, Pristiyanilicia (Smart Education, 2024)
Abstract: Healthy and wise use of the internet is an important factor in forming a superior generation in the current era of digitalization. This Community Service activity educates participants on how to use the internet healthily to support individual and community development towards achieving a superior young generation in Cengkering Pekan Village, Batubara Regency. The PKM activity method is in the form of socialization to participants by explaining several aspects, starting from digital literacy, introduction and use of the internet, and social media, to the impact of internet use on life. Healthy internet use can improve critical thinking abilities, creativity, and technical skills, all of which are the main components of a superior generation. In addition, education regarding digital ethics and cyber security has proven effective in reducing the risks associated with unwise internet use. The results of this PKM activity conclude that collaboration between the government, educational institutions, and the community is very necessary to promote healthy internet use to create a competent generation, that has integrity and is highly competitive in the future. Keywords: healthy internet; superior generation; cengkering pekan village. Abstrak: Penggunaan internet yang sehat dan bijaksana merupakan faktor penting dalam membentuk generasi unggul di era digitalisasi saat ini. Kegiatan Pengabdian Masyarakat ini memberikan edukasi kepada para peserta kegiatan bagaimana pemanfaatan internet sehat dalam mendukung perkembangan individu dan masyarakat menuju pencapaian generasi muda unggul yang ada di Desa Cengkering Pekan Kabupaten Batubara. Bentuk metode kegiatan PKM ini berupa sosialisasi kepada para peserta dengan memaparkan beberapa aspek, mulai dari literasi digital, pengenalan dan penggunaan internet, sosial media, hingga dampak penggunaan internet terhadap kehidupan. Dalam penggunaan internet yang sehat dapat meningkatkan kemampuan berpikir kritis, kreativitas, dan keterampilan teknis, yang semuanya merupakan komponen utama dari generasi unggul. Selain itu, edukasi mengenai etika digital dan keamanan siber terbukti efektif dalam mengurangi risiko yang terkait dengan penggunaan internet yang tidak bijak. Adapun hasil kegiatan PKM ini menyimpulkan bahwa kolaborasi antara pemerintah, institusi pendidikan, dan masyarakat sangat diperlukan untuk mempromosikan pemanfaatan internet sehat guna menciptakan generasi yang kompeten, berintegritas, dan berdaya saing tinggi di masa depan. Kata kunci: internet sehat; generasi unggul; desa cengkering pekan